Natural history of cervical intraepithelial neoplasia-2 in HIV-positive women of reproductive age - Colie, Christine (J Acquir Immune Defic Syndr, 2018)
OBJECTIVE: To evaluate the natural history of treated and untreated cervical intraepithelial neoplasia-2 (CIN2) among HIV-positive women. METHODS: Participants were women enrolled in the Women’s Interagency HIV Study between 1994 and 2013. 104 HIV-positive women diagnosed with CIN2 before age 46 were selected, contributing 2,076 visits over a median of 10 years (IQR 5–16). The outcome of interest was biopsy-confirmed CIN2 progression, defined as CIN3 or invasive cervical cancer. CIN2 treatment was abstracted from medical records. RESULTS: The majority of women were African American (53%), current smokers (53%) and had a median age of 33 years at CIN2 diagnosis. Among the 104 HIV-positive women, 62 (59.6%) did not receive CIN2 treatment. Twelve HIV-positive women (11.5%) showed CIN2 progression to CIN3; none were diagnosed with cervical cancer. There was no difference in the median time to progression between CIN2-treated and -untreated HIV-positive women (2.9 vs. 2.7 years, p=0.41). CIN2 treatment was not associated with CIN2 progression in multivariate analysis (aHR [adjusted hazard ratio] 1.82; 95% CI [confidence interval] 0.54, 7.11), adjusting for combination antiretroviral therapy (cART) and CD4+ T cell count. In HIV-positive women, each increase of 100 CD4+ T cells was associated with a 33% decrease in CIN2 progression (aHR 0.67; 95% CI 0.47, 0.88), adjusting for CIN2 treatment and cART. CONCLUSIONS: CIN2 progression is uncommon in this population, regardless of CIN2 treatment. Additional studies are needed to identify factors to differentiate women at highest risk of CIN2 progression.